Cat Kid comic club. Collaborations - Pilkey, Dav, 1966- (New York, NY : Graphix, 2022)
Excitement and imagination run wild as Naomi, Melvin, Poppy, Gilbert, Curly, and their siblings get back to making comics with originality and laughter. But wait--have they cleaned their rooms yet?!
3.3
3-6
GN290L
Keywords: Cats -- Comic books, strips, etc; Cats -- Juvenile fiction; Frogs -- Comic books, strips, etc; Frogs -- Juvenile fiction; Clubs -- Comic books, strips, etc; Clubs -- Juvenile fiction; Drawing -- Technique -- Comic books, strips, etc; Drawing -- Technique -- Juvenile fiction; Creative ability -- Comic books, strips, etc; Creative ability -- Juvenile fiction; Humorous stories; Graphic novels; Cats -- Fiction; Frogs -- Fiction; Clubs -- Fiction; Drawing -- Technique -- Fiction; Creative ability -- Fiction; Humorous comics; Comics (Graphic works); Graphic novels